Social wellbeing among women living with cancer - Ni Putu Wulan Purnama Sari (Intelektual Pustaka Media Utama, 2020)
Women living with cancer are gradually increases in number due to the increase prevalence of breast and cervical cancer worldwide. The social impact of cancer is underappreciated compared to physical and psychological impacts. This study aimed to: 1) compare and analyze the social wellbeing (SWB) between women living with breast and cervical cancer, and 2) determine the best predictor of SWB in both groups. This cross-sectional study involved 58 and 47 women living wih breast and cervical cancer (n=105). Questionnaire of QOL-CS part III was used in data collection. Various statistical tests were used in data analysis (α<0.05). Sufficient SWB was mostly found in both cases. Family stress, work life, home activities, worriness, social support, personal relation, sexuality, social isolation, and financial burden were significantly different between cases (p=0.021, p=0.027, p=0.004, p=0.022, p=0.000, p=0.000, p=0.000, p=0.000, and p=0.001 respectively), resulted in significant difference in overall SWB between cases (p=0.000). Home activities were the best predictor of SWB in both cases (R2=0.680 and R2=0.840 respectively) with more influences on cervical cancer (84% of influence). SWB was better in women living with breast cancer.